Socialist register 2009 : violence today : actually-existing barbarism - Panitch, Leo, 1945 -; Leys, Colin, 1931 - (Κοινωνικές επιστήμες = Social sciences, 2009)
Today, even after the slaughter of two world wars, the genocide of European Jewry and the creation of the United Nations, the world has often seemed no less violent than before. The contemporary forms of violence are so varied and complex, occurring at such different levels and in such widely different contexts, that their specific links to capitalism and imperialism need a fresh understanding. This volume paints on a broader canvass, with most of the essays analyzing the nature and roots of paradigmatic cases and types of violence today around the world.